ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG BUNGA DI DESA SIBANGKAJA, KECAMATAN ABIANSEMAL, KABUPATEN BADUNG - Sumantri, Putu Wanda Ayu; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The purpose of this study was to analyze the variables of capital, work experience, working hours and religious holidays simultaneously and partially on the income of flower traders in Sibangkaja Village, Abiansemal District, Badung Regency. The data used in this study is primary data which was taken as a sample of 86 respondents in Sibangkaja Village, Abiansemal District, Badung Regency. The analytical technique used in this research is descriptive analysis and multiple linear regression analysis techniques. The results of the study indicate that simultaneously showing capital, work experience, working hours and religious holidays have a positive and significant effect on the income of flower traders in Sibangkaja Village, Abiansemal District, Badung Regency. Partially, it shows that capital, work experience and religious holidays have a positive and significant effect on the income of flower traders in Sibangkaja Village, Abiansemal District, Badung Regency. The variable working hours partially has a positive relationship but has no significant effect on the income of flower traders in Sibangkaja Village, Abiansemal District, Badung Regency.